Combination of wavelength dispersive X‐ray fluorescence analysis and multivariate statistic for alluvial soils classification: a case study from the Padanian Plain (Northern Italy). (17th February 2014) - Di Giuseppe, Dario; Bianchini, Gianluca; Faccini, Barbara; Coltorti, Massimo
<x xml:space="preserve">Abstract</x> Wavelength dispersive X‐Ray fluorescence analysis, coupled with multivariate statistics, has been used to characterise the alluvial soils of the easternmost Po Plain area. Coarse to fine sediments, which can be related to various depositional environments (paleochannels, interfluvial areas, brackish marsh interdistributary bays and littoral dunes), have been taken into consideration. Through the use of an extensive analytical database and the principal component analysis in combination with factorial analysis, a soil classification method is proposed, which can also help to constrain the depositional environment of the alluvial sediments. This methodology was subsequently validated using other wavelength dispersive X‐Ray fluorescence analyses of soils with different provenance and historical bricks made with alluvial deposits similar to those already studied. By relating the principal component analysis in combination with factorial analysis factors, we therefore provide a useful tool to integrate the classical and well‐established classification of alluvial deposits based on field observation and grain size investigations. Copyright © 2014 John Wiley & Sons, Ltd.